(untitled) (International Journal of Engineering and Computer Science, 2015)
The ever increasing demand of communication equipment and the emergence of new technologies require an efficient design of antenna that is of smaller size for wider range of frequency for ISM Band application such as W-LAN. The (ISM) bandranges from 2 GHz to 2.8 GHz which also include WLAN according to IEEE 802.11g standard that extended throughput to up to 54 Mbit/s using the same 2.4 GHz band. Because of the various advantages like low profile, ease of integration, low cost etc. Microstrip antenna found vast application in communication system. Here we report the investigation on Planar antenna using probe feed technique. Analysis is done on the two different substrate i.e. FR-4 and RT Duroid 5880 with dielectric constant 4.3and 2.2 respectively with introduction of a horizontal slit along the width of the patch. The antenna is simulated using CST (Computer Simulation Technology) microwave studio v.2011 and the antenna parameters like return loss, VSWR, Gain, Bandwidth have been analyzed. The design procedure for patch antenna for ISM Band application is illustrated.